Non-clinical determinants of Medevacs in Nunavut: perspectives from northern health service providers and decision-makers. Issue 1 (1st January 2019) - McDonnell, Leah; Lavoie, Josée G.; Healy, Gwen; Wong, Sabrina; Goulet, Sara; Clark, Wayne
ABSTRACT: A medevac involves the transport of a critically ill patient, usually by plane or helicopter, to access necessary and at times life-saving care, most often only accessible in urban centres. Medevacs are commonly used in resource-limited and geographically isolated areas in Canada. The objective of this study was to explore the determinants of medevac decision-making from the perspective of frontline care providers and decision-makers in Nunavut. For this purpose, we conducted a secondary analysis of 90 in-depth interviews. Findings indicate that medevacs can be the result of a number of intersecting factors, including the referring and receiving provider's experience, insufficient staffing in health centres, lack of access to diagnostic or treatment-related, and challenges related to recruitment and retention. An expanded scope of practice for frontline care providers, and a related lack of training and/or confidence in skills, only add to these challenges. Medevacs play an important role related to managing shifting community nursing workloads, which expands and contracts in response to local needs. Attention to structural issues, putting in place virtual peer support systems, resolving vacancies left by the lag between attrition and recruitment, increasing access to training, and local diagnostic and treatment equipment, might decrease reliance of medevacs.